A Rare Complex Case Report: Bilateral Congenital Internal Carotid Artery Hypoplasia Associated with Ruptured Left True Posterior Communicating Artery Aneurysm - Soni, Tushar V.; Patel, Shreyansh; Shah, Varshesh; Deo, Manas Ranjan; Kotadiya, Kuldeep (Asian Journal of Neurosurgery, 2024)
Congenital internal carotid artery hypoplasia is a rare condition characterized by underdevelopment or reduced caliber of the internal carotid artery during embryonic development. This anomaly presents significant challenges in management, particularly in neurosurgical interventions for cerebrovascular events. We present a case report of a 67-year-old male who presented with subarachnoid hemorrhage and intraparenchymal hemorrhage extending as intraventricular hemorrhage due to a ruptured left true posterior communicating artery aneurysm, associated with intraoperative findings of left internal carotid artery aneurysm, accompanied by incidental findings of bilateral congenital hypoplasia of the internal carotid artery on computed tomography angiography. Surgical intervention involved a left frontotemporal craniotomy, during which both aneurysms were successfully clipped. This case underscores the critical importance of meticulous preoperative evaluation, utilizing advanced neuroimaging modalities to identify such anomalies, particularly in patients with acute cerebrovascular events. Furthermore, it emphasizes the necessity for meticulous surgical planning and intraoperative vigilance to effectively manage associated vascular pathologies.
Keywords: congenital internal carotid artery hypoplasia; cerebrovascular anomalies; neurosurgical interventions; aneurysm; bilateral